Damage detection in a reinforced concrete bridge applying wavelet transform in experimental and numerical data - ramon saleno yure rubim costa silva; Erwin U. L. Palechor; Luciano M. Bezerra; Marcus V. G. de Morais; Welington V. da Silva (Fracture and Structural Integrity)
In recent years, one can observe a constant worry of the scientific community on the search for demage detection techniques in structures. Such worry contributed to the progressive development of Structural Health Monitoring. This paper purpose a methodology using Continuous Wavelet Transform associated with interpolation and regularization techniques applied in the experimental and numerical mode shapes of the Dogna Bridge using only the demaged responses. The results of the analyses are presented and discussed in this paper.